EFFECTIVENESS OF PARENTAL HOLDING TERAPHY AND MUSICAL TERAPHY TO REDUCE PAIN SCALES IN INFANT DURING MEASLES IMMUNIZATION - Fitri Wahyuni; Ulfa Suryani (Nurse and Health: Jurnal Keperawatan, 2020)
Background: Cases of measles in Indonesia are among the 10 biggest diseases that occur in children aged 29 days - 4 years. At the age of 9 months the infant must get immunizations that can be given by subcutaneous which can give the baby pain experience.Objectives: The purpose of this study was to determine the effectiveness of parental holding therapy and music therapy to reduce pain scales in the infants during measles immunization.Methods: This type of research is quasy experiment with the pretest and posttest approach without control of the design group. The sampling technique in this study used a "purposive sampling" technique with a total sample of 24 respondents and research instruments using the FLACC scale observation sheet. The data were analyzed using computerization with an independent paired t-test with a confidence level of 95%, α < 0.05.Results: The results of this study indicate that the average reduction in pain scale before and after parental holding therapy is 4.2 while music therapy is 2.7. It was concluded that parental holding therapy more effectively to reducing the scale of pain in infants during measles immunization in Kubu Dalam Parak Karakah Village, Working Area of Public Health Center of Andalas, Padang City in 2019 with p-value = 0.017 (p <0.05).Conclusion: It is recommended that health workers be able to apply and find out the benefits and effects that are felt from parental holding therapies and music therapy so that parents do not feel afraid in giving therapy. Keywords: Measles Immunization, Music Therapy, Pain, Parental Holding Therapy